Aplikasi E-Commerce F&B pada Azzam’s Kitchen Berbasis Web: Studi Kasus pada Azzam’s Kitchen - Azizah Nur Afifah Amanta; Riki Purba (Jurnal Penelitian Multidisiplin Ilmu, 2023)
Azzam's Kitchen is a business unit that sells homemade food. The procurement transaction process and procurement records still use a paper system and have not been integrated with a database system. Manual systems at Azzam's Kitchen cause several problems in purchasing transactions such as being vulnerable to loss or damage in data purchase transactions, by filling in twin data, reports take time because they have to process the data first and food stock inventory that cannot be known at any time. Based on these problems, an e-commerce application is designed and built on a web-based food Azzam's kitchen, which is a system which is designed to check and find out master data, process transaction data, perform structured transactions, search for food data, fill in twin data, reports that take time because they have to process data and food stock inventory that cannot be known at any time.With a web-based system for developing a food business, this application can carry out the purchasing process and have a website, for a food business unit that is well organized so that the system works in a structured manner and can be implemented.